Subpixel stacking and detection of blurred star images observed by an astroinertial attitude sensor against the background of the daytime sky - N.N. Vasilyuk (Компьютерная оптика)
To determine the attitude from the image of a star field obtained by a digital camera, it is necessary to detect images of individual stars and determine their coordinates with subpixel resolution. This problem is relatively easy to solve if the image of the star field is obtained by a stationary camera observing a clear night sky. The difficulty arises when the stars are observed by the rotating camera against the background of the daytime sky. The blurred images of stars are almost impossible to detect in the background noise in one frame. This difficulty can be overcome by accumulating a certain number of consecutive frames after the matched blur filtering has been performed. This paper considers an algorithm for accumulating the sequence of frames, implemented as a multichannel accumulator, consisting of several accumulative channels of the same type, and operating in parallel. The plane of the accumulated image in each channel coincides with the plane of the first frame of the accumulated sequence. Subpixel resolution in determining the coordinates of detected star images is achieved by introducing intrapixel discretization in the first frame. The orientation of the current frame relative to the first one is calculated from the measurements of the gyroscopes of the astroinertial sensor. When synthesizing the impulse responses of the blur-matched filters for the current frame, the attitude of this frame and the location of the intrapixel discretization nodes of the first frame are taken into account. Calculation formulas are given for determining the number of accumulated frames depending on the angular velocity of the camera rotation, the background intensity and the brightness of the observed stars. The simulation results show the possibility of detecting blurred images of fairly dim stars against the background of the daytime sky and determining their coordinates with subpixel resolution.